Dr. Efficacy of Mindfulness Meditation on Mental Health during the times of COVID’19- A Mixed-Method Study: Mindfulness meditation during COVID’19 - Khandelwal, Sarika (IJRDO- Journal of Educational Research, 2020)
The current study aims to evaluate the impact of a two-week online Mindfulness Meditation (MM) intervention on levels of Depression, Stress, and Anxiety and gain insights into participants' motivation and experiences of the intervention. Twenty-five participants (16 females & 9 males) were recruited through web-based advertisement using a random purposive sampling technique. DAS scale was administered before and after the intervention period to identify quantitative changes over time. Further, ten participants (6 females & 4 males) who exhibited significant changes in their quantitative measures were interviewed via video conferencing to understand the particular motivators and experiences of participating; where the responses were analyzed using Interpretative Phenomenological Analysis.  Change in outcome measures over time was examined using Mean, S.D., and paired t-test.Results revealed significant improvements in reducing the severity of depression, anxiety, and stress symptoms significantly (all p >0.001) and improvement was sustained at three month follow- up. The qualitative analysis depicted Spiritual inclination and Experience of stress and loneliness as motivation themes for enrolling. Moreover, lived experience of the participants exhibited three overarching themes – a. self- awareness, b. insight development, c. social cohesion.The study provides evidence in support of the effectiveness of brief, MM in a non-clinical population and suggests that low-intensity intervention can be used for modulating negative psychological states through easily accessible and non- physical contact training mode. However, more research is needed to confirm and better understand these results and to test the potential of such interventions.Keywords:  COVID-19, Mindfulness Meditation, psychological well-being